The Association of Neutrophil/Lymphocyte and Platelet/Lymphocyte Ratios and Hematological Parameters with Diagnosis, Stages, Extrapulmonary Involvement, Pulmonary Hypertension, Response to Treatment, and Prognosis in Patients with Sarcoidosis - Celalettin Korkmaz; Sinan Demircioglu (Canadian Respiratory Journal)
Sarcoidosis is a rare disease characterized by granulomatous inflammation in affected organs, primarily in lungs. Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) are easy and practical methods providing valuable information in diagnosis, severity, and prognosis of various diseases. Here, we aimed to investigate the association between NLR, PLR, and hematological parameters in sarcoidosis. The study was performed with 75 sarcoidosis patients and 92 controls. Patients’ NLR, PLR, and hematological parameters were compared with those of controls. Additionally, while differences between NLR and PLR were investigated in sarcoidosis patients, differences of extrapulmonary involvement, pulmonary hypertension (PH), and spontaneous remission between those with and without responses to treatment concerning stages were also assessed. NLR and PLR were significantly higher in sarcoidosis patients than controls. For NLR, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were found as 68, 61, 58, and 70% respectively, while sensitivity, specificity, PPV, and NPV for PLR were found as 72, 67, 63, and 74%, respectively. In sarcoidosis patients, NLR and PLR were significantly higher at stage-2 and -3 than at stage -1 and -4. There was a significant weak positive correlation between C-reactive protein (CRP) and NLR and PLR. Mean platelet volume (MPV), hemoglobin (Hgb), and mean corpuscular volume (MCV) were lower among patients than controls. A positive moderate correlation was detected between NLR and CD4/CD8 in blood, while there was a strong positive correlation between CD4/CD8 in bronchoalveolar lavage (BAL) and positive moderate correlation between PLR and CD4/CD8 in BAL. High NLR and PLR values were not significantly associated with pulmonary PH, spontaneous remission, response to treatment, and prognosis. The increase in PLR and NLR may be a guide for diagnoses of both sarcoidosis and lung parenchymal involvement. To use these entities as markers, our findings should be supported with prospective studies with larger samples.